Pregnancy outcomes in women with neurofibromatosis 1: a Danish population-based cohort study. Issue 3 (25th January 2021) - Kenborg, Line; Boschini, Cristina; Bidstrup, Pernille E; Dalton, Susanne O; Doser, Karoline; Nielsen, Thomas T; Krøyer, Anja; Johansen, Christoffer; Frederiksen, Kirsten; Sørensen, Sven Asger; Hove, Hanne; Østergaard, John R; et al.
Abstract : Background: The probability of a pregnancy, live birth, stillbirth and abortion has never been assessed in women with neurofibromatosis 1 (NF1) in a large population-based study. Methods: We included 1006 women (15–49 years) registered with NF1 in the Danish National Patient Registry or followed in two national Centers for Rare Diseases and 10 020 women from the Danish population. Information on pregnancy outcomes was ascertained from health registries. Cumulative incidence, mean cumulative count, hazard ratios (HRs) and proportion ratios (PRs) with 95% CIs were calculated. Results: The cumulative incidence of a first pregnancy at age 50 years was slightly lower in women with NF1 (74%; 95% CI 70 to 77) than in population comparisons (78%; 95% CI 77 to 79). When all pregnancies were included, two pregnancies were expected per woman at age of 50 years, irrespective of a NF1 diagnosis. The hazard of a pregnancy did not differ between women with NF1 (HR 1.03; 95% CI 0.95 to 1.11) and the comparisons after adjustment for somatic and psychiatric disease. The proportion of pregnancies that resulted in a live birth was 63% (783/1252) among women NF1 and 68% (8432/12 465) among the comparisons, yielding a PR of 0.95 (95% CI 0.90 to 1.00). The proportions of stillbirths (PR 2.83; 95% CI 1.63 to 4.93) and spontaneous abortions (PR 1.40; 95% CI 1.09 to 1.79) were increased in women with NF1. Conclusions: A similar hazard for pregnancy was observed for women with NF1 and population comparisons after adjustment for potential medical consequences of NF1. However, women with NF1 experienced more spontaneous abortions and stillbirths.